2015
DOI: 10.1177/0309364614543550
|View full text |Cite
|
Sign up to set email alerts
|

The effects of orthoses, footwear, and walking aids on the walking ability of children and adolescents with spina bifida

Abstract: This is the first evidence-based systematic review of the efficacy of assistive devices for gait and walking outcomes for children with spina bifida. The ICF-CY is used as a reference framework to differentiate the effects of treatment on gait parameters, walking capacity, and walking performance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
26
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(27 citation statements)
references
References 32 publications
0
26
0
1
Order By: Relevance
“…The latest version of NSBPR now includes information about assistive device and orthoses which should help drive future research related to ambulation. A recent systematic review 22 revealed that crutches and ankle foot orthoses do provide some benefits for gait pattern, stride, and oxygen cost but research on the functional benefits of orthoses and assistive devices in SB is quite limited.…”
Section: Discussionmentioning
confidence: 99%
“…The latest version of NSBPR now includes information about assistive device and orthoses which should help drive future research related to ambulation. A recent systematic review 22 revealed that crutches and ankle foot orthoses do provide some benefits for gait pattern, stride, and oxygen cost but research on the functional benefits of orthoses and assistive devices in SB is quite limited.…”
Section: Discussionmentioning
confidence: 99%
“…Ankle-foot orthosis (AFO) is a specially designed supportive medical device which is intended to i) control the motion of the ankle and subtalar joints, ii) compensate for muscle weakness and drop foot, iii) correct deformities in the ankle and subtalar joints due to injuries [1] and [2], stroke [3] and [4], and congenital anomalies such as cerebral palsy [5] to [7] and spina bifida [8] and [9]. Many different types of AFO are available for different biomechanical and clinical purposes.…”
Section: Introductionmentioning
confidence: 99%
“…4 The KAFOs are less frequently used in these populations, and very few publications found report on the efficacy of this modality of orthotic management. 2,4,5 Few reviews or systematic…”
mentioning
confidence: 99%
“…5 In addition, no literature has been found to compare different variants of orthoses (molded and conventional) with barefoot conditions. In this report, we present a case of an ambulant adolescent case of myelomeningocele, who received orthoses and was compared with different bracing conditions.…”
mentioning
confidence: 99%